EXPERIMENTAL INVESTIGATION ON 4-S CI ENGINE USING PUMPKIN SEED BIO-DIESEL AS AN ALTERNATIVE FUEL BY VARYING THE INJECTION TIMING (International Journal of Food and Nutritional Sciences, 2022)
Bio fuel, which comes from renewable resources, burns cleanly. Bio fuel can replace diesel in compression-ignition engines. A diesel engine with PSBO and diesel mixes was used to examine how Optimal injection timing improves efficiency and reduces pollution.The injection timing was adjusted from what is typically used with diesel oil. The diesel engine used for the tests was a single cylinder, direct injection, four stroke design.According to the data, the best performance and lowest emissions are achieved at an injection timing of 27°bTDC.